2012
DOI: 10.1007/s13238-012-2006-9
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of sigma-1 receptor inhibits ADAM10 and ADAM17 mediated shedding in vitro

Abstract: The sigma-1 receptor is a molecular chaperone protein highly enriched in the brain. Recent studies linked it to many diseases, such as drug addition, Alzheimer's disease, stroke, depression, and even cancer. Sigma-1 receptor is enriched in lipid rafts, which are membrane microdomains essential in signaling processes. One of those signaling processes is ADAM17-and ADAM10-dependent ectodomain shedding. By using an alkaline phosphatase tagged substrate reporter system, we have shown that ADAM10-dependent BTC shed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The sigma-1 receptor contains a cholesterol recognition domain in its C-terminus and is able to remodel lipid rafts by changing the relative distribution of cholesterol between raft and non-raft fractions (Takebayashi et al, 2004 ). Interestingly, overexpression of sigma-1 in HEK293 or COS cells diminished Betacellulin cleavage by ADAM10 further substantiating the lipid-sensitivity of the enzyme (Li et al, 2012 ). Several investigations also report on influence of different lipid species such as trans fatty acids on APP processing balance (e.g., Eckert et al, 2011 ; Grimm et al, 2012 ) but in this regard it is not clear if this has a direct influence on ADAM10 or whether indirect mechanisms are involved.…”
Section: Regulation Of Adam10mentioning
confidence: 74%
“…The sigma-1 receptor contains a cholesterol recognition domain in its C-terminus and is able to remodel lipid rafts by changing the relative distribution of cholesterol between raft and non-raft fractions (Takebayashi et al, 2004 ). Interestingly, overexpression of sigma-1 in HEK293 or COS cells diminished Betacellulin cleavage by ADAM10 further substantiating the lipid-sensitivity of the enzyme (Li et al, 2012 ). Several investigations also report on influence of different lipid species such as trans fatty acids on APP processing balance (e.g., Eckert et al, 2011 ; Grimm et al, 2012 ) but in this regard it is not clear if this has a direct influence on ADAM10 or whether indirect mechanisms are involved.…”
Section: Regulation Of Adam10mentioning
confidence: 74%
“…We found that immature LSECs fail to release HB‐EGF due to a deficiency in the sheddases needed to release the HB‐EGF ectodomain from the cytosolic membrane. The sheddases ADAM12, ADAM17, ADAM32, ADAM33, ADAMTS1, and ADAMTS4 are down‐regulated in the immature LSEC, which explains why these cells are unable to maintain HSC quiescence.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: EGFR, epidermal growth factor receptor; FFA, free fatty acid; MMP, matrix metalloproteinase. the immature LSEC, (37)(38)(39)(40)(41)(42) which explains why these cells are unable to maintain HSC quiescence.…”
Section: Discussionmentioning
confidence: 99%
“… 56 Finally, the sigma 1 receptor is enriched with lipid raft markers, and their functions are tightly connected. 57 Directly, S100 as an adaptor protein has been found to interact with serotonin and dopamine receptors, causing an increased localization of the 5-HT 1B and 5-HT 4 receptors to the plasma membrane, 19 modulates serotonin neurotransmission, 58 and enhances D 2 receptor signaling. 59 Based on the current work, the exact mechanism should continue to be explored.…”
Section: Discussionmentioning
confidence: 99%